Speculation vis a vis Faith and Reason in Islam and Christianity: Medieval attempts at incorporating Reason with Revelation. - Pawan Ahmad, Isham (Common Ground Publishing, 2007)
• Abstract: Medieval philosophers were confident that they must and could interpret and assimilate philosophy i.e. Greek philosophy into the religious ethos. The medieval philosophers' reasoning on why it was necessary to incorporate philosophy into the religious ethos is because philosophy provided the proofs for theoretical opinions in religion. For the Muslim philosophers, its major proponent, al-Farabi, sees revelation as the ultimate culmination of the highest intellectual truths transformed and put into a symbolic language with power to motivate man to right action. Revelation is capable to be understood by all and more importantly to drive and commit them to action. Aquinas adds a Christian dimension to this debate on the relationship of revelation to reason through his arguments for natural law. The need to investigate the relationship of revelation and reason and from this its implications on natural law and the future of the development of ethics has now an added dimension and importance.